Human rights in Deuteronomy: with special focus on slave laws - Tsai, Daisy Yulin (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2014)
The Term????? in Exod 21:7The Special Marital Sale and Redemption in Exod 21:7-11; The Term?????????? in Dt 15 and the Terms???? and????? in Ex 21 Denote Different Situations; Reading the Law in Its Context; Dissimilar Accounts and Ceremonies for a Permanent Slave; The Value and the Interest That the Law Promotes and Protects; Similar Ceremonies with Different Expressions; Discerning the Similarities and Differences between Dt 15 and Ex 21 with the Legal Categorizational System; Deut 15:12-18 and Lev 25:39-55; The Different Length of Term in Lev 25; The Types of Debt Slave in Lev 25